Economic costs associated with acute attacks and long-term management of hereditary angioedema - Wilson, David A; Bork, Konrad; Shea, Elizabeth P; Rentz, Anne M; Blaustein, Marc B; Pullman, William E (Annals of allergy, asthma, & immunology, 2010)
Hereditary angioedema (HAE) is a rare autosomal dominant disorder characterized by recurrent acute attacks of swelling of the larynx, abdomen, and periphery. To assess the economic burden associated with acute attacks and long-term management of HAE. Burden was assessed via a Web-based survey of HAE patients (> or = 18 years old) that solicited information on attack characterization, short-term treatment, long-term disease management, impact on work, and patient costs. A standardized instrument, the Work Productivity and Activity Impairment questionnaire, was included to assess impact on work productivity. Standard medical costs and US average wage costs were assigned to survey items to assess direct medical and indirect costs, respectively. Total annual per-patient costs are estimated at $42,000 for the average HAE patient, with costs totaling $14,000 for patients with mild attacks, $27,000 for patients with moderate attacks, and $96,000 for patients with severe attacks. Hospital costs account for 67% of direct medical costs. Respondents reported high rates of missed work, lost productivity, and lost income, contributing to indirect costs totaling $16,000 annually for the average patient. Almost all costs increase with disease severity, although the distribution varies with severity: indirect costs account for 75% of costs for patients with mild attacks, whereas emergency department and hospital costs account for 68% of costs for patients with severe attacks. HAE results in considerable economic burden to patients, payers, and society in terms of direct medical and indirect costs and compounds the substantial humanistic burdens, which will be reported separately.